VD_FINDINFO AI 258/10 - 351/2011 vom 18. Juli 2011 - VD Tribunal cantonal (2011)
ATTEINTE À LA SANTÉ PSYCHIQUE, RECONSIDÉRATION, ADMISSION DE LA DEMANDE | 28 al. 2 LAI, 4 LAI, 16 LPGA, 53 al. 2 LPGA, 53 LPGA, 8 al. 1 LPGA, 26 al. 1 RAI, 26 RAI